Chemical Composition Ananlysis of Coconut Shell Powder and Ash for Composite Reinforcement. - Abba-Aji, M. A.; Ameh , E. S.; Shuwa, M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The use of natural resources which are environmentally friendly to replace the conventional composites materials had been the interest of many researchers lately. Beside the use of natural fibres as reinforcement in polymer matrix composites, the use of fillers made from natural sources such as coconut shell, corn cobs, palm kernel shell, rice husk, has been confirmed to be potential material that can offer some good properties to satisfy the requirements needed for some engineering applications. In this study, the potential of coconut shell powder and coconut shell ash were investigated. Fourier transform infra-red spectroscope was used to determine the chemical compositions of the samples. The results obtained revealed that coconut shell powder and coconut shell ash demonstrated comparable chemical properties to the conventional composites. The presence of some basic elements which are required to produce reinforcement materials with high strength, durability, light weight and corrosion resistance were confirmed. The results obtained revealed that coconut shell powder and coconut shell ash could be used as composites and other polymer matrix that are required for engineering applications